2015
DOI: 10.21608/jacb.2015.48405
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Genetic Components by Using Triallel Crosses Mating Design

Abstract: This investigation carried out to determine combining ability and types of gene action for yield component traits and some fiber properties in cotton. The genetic materials in this investigation included six cotton varieties i.e. G.85 (P1) ; Kar. (P2) ; G.93 (P3); Pima S7 (P4) Aust.12 (P5) and G.86 (P6). All these varieties belong to the species Gossypium Barbadense L. and they were utilized in a trialed crosses mating design to produce 60 hybrids. In 2013 growing season all genotypes which included 60 genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The good x good GCA combination could be due to additive and additive types of gene action which is fixable on nature which had significant SCA effects for studied traits. Yahia [32]; Sorour et al [33], Chinchane et al [26] and Yehia and EL-Hashash [34]. This study suggested that information of GCA effects of parent should be considered along with SCA effects and presence performance of hybrid for predicting the value of any hybrid.…”
Section: Specific Combining Ability (Sca) Effectsmentioning
confidence: 81%
“…The good x good GCA combination could be due to additive and additive types of gene action which is fixable on nature which had significant SCA effects for studied traits. Yahia [32]; Sorour et al [33], Chinchane et al [26] and Yehia and EL-Hashash [34]. This study suggested that information of GCA effects of parent should be considered along with SCA effects and presence performance of hybrid for predicting the value of any hybrid.…”
Section: Specific Combining Ability (Sca) Effectsmentioning
confidence: 81%